Transient simulation of dynamic buckle propagation of a shallow cylinder under external pressure with damping. Issue 3 (February 2021) - Yan, Sunting; Cheng, Mao; Ling, Zhangwei; Jin, Zhijiang
Abstract: This paper presents a finite element simulation of transient buckle propagation of shallow elastic cylinder under time dependent external pressure load considering the effect of damping. We conclude that by assigning transient pressure a value slightly smaller or larger than static buckle propagation pressure the buckle propagation directions can be reversed.